A study on prevalence of overweight and obesity in school going adolescents and its association with socio-demographic factors in Lucknow district - Mishra, Sudhanshu; Gupta, Pratibha; Srivastava, Mrinal Ranjan; Sachan, Beena; Zaidi, Zeashan Haider (International Journal Of Community Medicine And Public Health, 2019)
Background: Overweight and obesity are defined as abnormal or excessive fat accumulation that presents a risk to health. Obesity has become a global public health issue and is widely recognized as a key risk factor for coronary heart disease, hypertension, diabetes and many other health problems. The objectives of present study were to assess the prevalence of overweight and obesity and its association with socio-demographic factors amongst school-going adolescents in Lucknow district. Methods: This study was a school-based cross-sectional study and was carried out in urban and rural areas of Lucknow, from January 2018 to June 2018. Sample size was 620. A multi-stage random sampling technique has been used to select the required sample size. Data analysis was done using software MS Office excel and SPSS 18 for windows. Results: A total of 620 adolescents were studied. Majority (82.1%) of adolescents were found to be non-overweight/obese while 17.9% were found to be overweight/obese. Majority (66.7%) of students were overweight or obese, belonging to social class I while only 15.7% students were overweight or obese belonging to social class V. Conclusions: The results of our study show that overweight/obesity continues to be a public health concern in adolescents. The current study shows that adolescent overweight and obesity are increasing even in low socio-economic status. Emphasis should be placed on awareness program for obesity prevention among school students by strengthening lifestyle change.